Distribution and Movements of Brood-rearing Lesser Snow Geese in Relation to Petroleum Development in Arctic Alaska - Johnson, Stephen R. (ARCTIC, 1998)
Environmental scientists were concerned that construction of the Endicott Project in the outer Sagavanirktok River delta, east of Prudhoe Bay, Alaska, would obstruct brood-rearing movements of Alaska's largest established nesting population of lesser snow geese (Chen caerulescens caerulescens). During 1980-84, prior to the Endicott Project, the distribution of snow goose flocks during the brood-rearing period was generally less than 5 km from the coast and 15 km from the nesting colony. Prior to development, the average distance between brood-rearing areas used during consecutive years by individual banded birds was 4.7±2.9 km (mean ±s.d.). After development commenced during winter 1984-85, the distribution of brood-rearing flocks expanded inland as far as 9 km and eastward as far as 32 km from the nesting colony. The average distance between brood-rearing areas used during consecutive years by individual banded birds was 8.0±7.5 km. The proportion of brood-rearing snow geese captured on the east side of the Endicott Road and Causeway (east of the nesting colony) during the post-construction years (1985-93) was not significantly different from the proportion using the same area before construction (1980-84). The hypothesis that the Endicott Road and Causeway obstructed eastward movements of brood-rearing snow geese can be rejected. Les spécialistes de l'environnement s'inquétaient que la construction du pont-jetée Endicott dans le delta externe du Sagavanirktok situé à l'est de Prudhoe Bay en Alaska puisse gêner les déplacements reliés à l'élevage des oisons de la plus importante population nicheuse de la petite oie des neiges (Chen caerulescens caerulescens) en Alaska. Durant la période allant de 1980 à 1984, soit avant le projet Endicott, la distribution des volées d'oies des neiges durant la période d'élevage de la couvée s'étendait en général à moins de 5 km de la côte et 15 km de la colonie nicheuse. Avant la mise en valeur, la distance moyenne entre les zones d'élevage des oisons utilisées durant des ...